2019
DOI: 10.1088/1361-6463/ab0598
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved characterization of plasma properties in a CH4/He nanosecond-pulsed dielectric barrier discharge

Abstract: Non-equilibrium plasmas for plasma-assisted combustion, pollutant remediation, fuel reforming, and catalysis rely on the production of energetic electrons that ionize, dissociate, and excite the fuel and oxidizer molecules. Experimental characterization of the electron temperature, electron density, and vibrational temperature are necessary to validate and improve plasma kinetic models. An experimental apparatus capable of Thomson scattering and vibrational Raman scattering measurements in the same discharge w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 45 publications
1
20
1
Order By: Relevance
“…We simultaneously vary the vibrational temperatures of CH 4 and O 2 between 500 and 1500 K and assume both vibrational temperatures to have the same value. Chen et al 62 measured the vibrational temperature in a CH 4 / N 2 /He DBD plasma at 60 Torr based on the ν = 1 peak of N 2 and observed a maximal vibrational temperature of 1350 K. We here choose an upper limit of 1500 K, which is still in the uncertainty range of the results from Chen et al 62 We choose this value to be an upper limit since the vibrational temperature measured by Chen et al was based on the ν = 1 peak of N 2 and the vibrational temperature of CH 4 is likely to be lower. As a comparison, Butterworth et al 63 studied the vibrational excitation of CH 4 in low-pressure pulsed microwave plasma and found that the vibrational and gas temperatures equilibrate around 900 K. In any case, varying the vibrational temperature in this wide range is interesting from a theoretical point of view as well.…”
Section: Resultsmentioning
confidence: 99%
“…We simultaneously vary the vibrational temperatures of CH 4 and O 2 between 500 and 1500 K and assume both vibrational temperatures to have the same value. Chen et al 62 measured the vibrational temperature in a CH 4 / N 2 /He DBD plasma at 60 Torr based on the ν = 1 peak of N 2 and observed a maximal vibrational temperature of 1350 K. We here choose an upper limit of 1500 K, which is still in the uncertainty range of the results from Chen et al 62 We choose this value to be an upper limit since the vibrational temperature measured by Chen et al was based on the ν = 1 peak of N 2 and the vibrational temperature of CH 4 is likely to be lower. As a comparison, Butterworth et al 63 studied the vibrational excitation of CH 4 in low-pressure pulsed microwave plasma and found that the vibrational and gas temperatures equilibrate around 900 K. In any case, varying the vibrational temperature in this wide range is interesting from a theoretical point of view as well.…”
Section: Resultsmentioning
confidence: 99%
“…The method introduced in this paper was implemented for low‐pressure discharge [ 23,24 ] and then was applied in moderate pressure conditions. [ 22 ] By adjusting the micrometer‐driven translation stages, a more precise alignment can be achieved for the mask placement. Compared with a triple grating spectrometer, the current setup requires fewer optics, which can increase transmission efficiency and reduce complexity.…”
Section: Resultsmentioning
confidence: 99%
“…Then, the recorded spectra can be corrected for the various transmission curves of the optical components such as the ICCD camera and the diffraction grating. [ 22 ] Besides, the transmission efficiency ratio of the polarizer to the longpass filter is determined by measuring the power of a DPSS laser (MGL‐III‐532) with the polarizer parallel to the laser polarization.…”
Section: Calibration Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that rapid localized heating in the boundary layer produced a microwave, similar to the experiment performed by Roupassov et al (2009). Some kinetic methods have been suggested to model the NS-DBD actuator effects (Orr et al 2021;Chen et al 2019). The kinetic approach requires computational cost and time; thus, simpler models have been suggested.…”
Section: Introductionmentioning
confidence: 87%